Tyrophagus putrescentiae Schrank 1781 - Cilbircioğlu, Cihan; Çobanoğlu, Sultan (Zenodo, 2019)
Tyrophagus putrescentiae Schrank, 1781 Width: 239.12 ± 0.62 (163.01–362.38), length: 392.54 ± 0.86 (248.16–550.89) (n = 10). Specimens examined Taşköprü / Centrum garlic storage, 7. V.2014 (5 ♀♀); Taşköprü / Tekev Village garlic storage, 14.XII.2014 (6 ♀♀, 3 ♂♂); Taşköprü / Centrum garlic storage, 26.I.2015 (53 ♀♀, 42 ♂♂); Taşköprü / Ağcıkişi Village (65 ♀♀, 113 ♂♂); Centrum / Uzunkavak Village garlic storage, 10.IX.2015 (13 ♀♀, 10 ♂♂); Hanönü / Erik Village, 20. V.2016 (2 ♀♀, 1 ♂); Centrum / Abay Village, 24. V.2016 (1 ♂). Comments This species, which is called the mildew mite, can be found to a wide range of food, plant and animal materials suitable for environmental conditions and is considered as a cosmopolitan storage pest with economic and health importance. It is a potential vector of parasitic fungi, such as Aspergillus flavus, A. fumigatus, A. niger, Mucor racemosus (Fresen) and Nectria haematococca (Wollenweber) (Zhang and Fan 2005). It was identified on head and green parts of garlic and storage samples andfound intensively in storages.

Published as part of Cilbircioğlu, Cihan & Çobanoğlu, Sultan, 2019, Phytophagous mite (Acari) species on garlic (Allium sativum L.) cultivation areas and storages of Kastamonu, Turkey, pp. 211-224 in Persian Journal of Acarology 8 (3) on page 217, DOI: 10.22073/pja.v8i3.46349, http://zenodo.org/record/7173998

{"references": ["Zhang, Z. - Q. & Fan, Q. - H. (2005) Revision of Tyrophagus Oudemans (Acari: Acaridae) of New Zeland and Australia. Landcare Research Contract Report, LC 0405 / 149, New Zealand Ltd., Auckland, New Zealand, 291 pp."]}
Keywords: Arthropoda; Arachnida; Animalia; Biodiversity; Sarcoptiformes; Tyrophagus; Tyrophagus putrescentiae; Taxonomy; Acaridae